Distinct Injury Responsive Regulatory T Cells Identified by Multi-Dimensional Phenotyping - Guo, Fei; Hancock, Brandon; Griffith, Alec; Lin, Hui; Howard, Kaitlyn; Keegan, Joshua; Zhang, Fan; Chicoine, Adam; Cahill, Laura; Ng, Julie; Lederer, James (Frontiers in Immunology, 2022)
CD4+ regulatory T cells (Tregs) activate and expand in response to different types of injuries, suggesting that they play a critical role in controlling the immune response to tissue and cell damage. This project used multi-dimensional profiling techniques to comprehensively characterize injury responsive Tregs in mice. We show that CD44high Tregs expand in response to injury and were highly suppressive when compared to CD44low Tregs. T cell receptor (TCR) repertoire analysis revealed that the CD44high Treg population undergo TCRαβ clonal expansion as well as increased TCR CDR3 diversity. Bulk RNA sequencing and single-cell RNA sequencing with paired TCR clonotype analysis identified unique differences between CD44high and CD44low Tregs and specific upregulation of genes in Tregs with expanded TCR clonotypes. Gene ontology analysis for molecular function of RNA sequencing data identified chemokine receptors and cell division as the most enriched functional terms in CD44high Tregs versus CD44low Tregs. Mass cytometry (CyTOF) analysis of Tregs from injured and uninjured mice verified protein expression of these genes on CD44high Tregs, with injury-induced increases in Helios, Galectin-3 and PYCARD expression. Taken together, these data indicate that injury triggers the expansion of a highly suppressive CD44high Treg population that is transcriptionally and phenotypically distinct from CD44low Tregs suggesting that they actively participate in controlling immune responses to injury and tissue damage.